2019
DOI: 10.1155/2019/8915272
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Hypolipidemic Activities of Acid-Depolymerised Exopolysaccharides by Termitomyces albuminosus

Abstract: The acid-depolymerised exopolysaccharides (ADES) of Termitomyces albuminosus were obtained, and the major fraction of ADES1 was isolated and purified by DEAE-52 cellulose anion-exchange column chromatography. Physicochemical characterizations showed that ADES1 was an α- and a β-configuration with the molecular weight of 2.43 kDa, containing (1→3, 4)-linked-Glcp, (1→4)-linked-D-Glcp, (1→3)-linked-D-Xylp, (1→4)-linked-D-Manp, T-Glcp, (1→6)-linked-D-Galp, and (1→4)-linked-L-Arap. The in vivo assays showed that AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The genus Termitomyces comprises ca. 34 species (He et al 2019), most of which are well-known for nutritional and medicinal values (Zhao et al 2019, Maity et al 2020. Fifteen Termitomyces species show a greyish to grey-brown pileus.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Termitomyces comprises ca. 34 species (He et al 2019), most of which are well-known for nutritional and medicinal values (Zhao et al 2019, Maity et al 2020. Fifteen Termitomyces species show a greyish to grey-brown pileus.…”
Section: Discussionmentioning
confidence: 99%
“…38,48 In vivo assays showed that polysaccharides from T. albuminosus extracted by ACE could reduce lipid levels in the serum and liver, decrease serum enzyme activities, and improve antioxidant enzyme activities and p-AMPKα expressions in hyperlipidemic mice. 15 A crude polysaccharide (THP-I) from T. heimii extracted by ALE (4% NaOH solution) has effectively diminished hyperplasia in 1,2dimethylhydrazine (DMH)-induced colon cancer of Swiss albino rats along with sprouting of goblet cells. 49 The studies show that the TPS obtained from acidic-or alkaline-aided extraction are likely to show promising biological activities.…”
Section: Extraction and Fractionation Ofmentioning
confidence: 99%
“…It cannot be cultivated, because a symbiotic relationship with termites is necessary [229,230]. The mushroom has been reported to contain water-soluble polysaccharides with a great variety of biological activities, including antioxidant, anti-inflammatory, hepatoprotective, hypolipidemic activities [230][231][232][233][234]. In addition, T. albuminosus has been reported to contain many other bioactive components, such as chitin-glucan complex, alkaline protease, saponins, melanin, lipids and ergosterol; some of which possess analgesic and anti-inflammatory activities [235][236][237][238].…”
Section: Termitomyces Albuminosus (Berk) R Heimmentioning
confidence: 99%
“…R. Heim, belonging to the family Lyophyllaceae is a very well-known wild edible mushroom, which is commonly distributed in Asia in China, Indonesia, Malaysia, and Singapore [4,228]. It cannot be cultivated, because a symbiotic relationship with termites is necessary [229,230]. The mushroom has been reported to contain water-soluble polysaccharides with a great variety of biological activities, including antioxidant, anti-inflammatory, hepatoprotective, hypolipidemic activities [230][231][232][233][234].…”
Section: Termitomyces Albuminosus (Berk) R Heimmentioning
confidence: 99%
See 1 more Smart Citation